Respuesta :
Answer:
Remainder= 5, and the binomial [tex](x-1)[/tex] is not a factor of the given polynomial.
Step-by-step explanation:
Given polynomial is [tex](2x^3-3x^2+6)[/tex] , we have to divide this with a binomial [tex}(x-1)[/tex] using remainder theorem.
Remainder theorem says if [tex](x-a)[/tex] is a factor then remiander would be [tex]f(a)[/tex]
Therefore for [tex](x-1), \ {we find}\ f(1)}[/tex]
[tex]f(1)=(2\times 1^3-3\times1^2+6)\\1^3 =1\\1^2=1\\Substituting \ this \ above\\f(1)= (2-3+6)=5[/tex]
Thus the remainder is 5 and since it is not 0 , so the binomial [tex](x-1)[/tex] is not a factor of the given polynomial.
Answer:
Remainder= 0 and it is a polynomial
Step-by-step explanation:
Got a 100% on edge 2020